The Templar lands in Lincolnshire in the early fourteenth century - Jefferson, Joseph Michael (2016)
The focus of the study is the Templar estates in Lincolnshire during the first four decades of the fourteenth century. Within this context, two themes are explored in some detail. The first theme is that of the characteristics of Templar farming and estate management as illustrated in the accounts of 1308-13 following the arrest of the Templars. The second theme is that of the fate of the former Templar properties between 1312 and 1338.